SEKUENS SPASIAL PADA GALERI SENI NUART SCULPTURE PARK, BANDUNG - Hanin Ayudhiya, Athaya; Aly, Sudianto (Jurnal Riset Arsitektur, 2025)
Abstract - A series of spatial arrangements that create a continuous path so that it has a starting and endingpoint can be referred to as a spatial sequence in architecture. The series of plots that play a role in conveyingthe concepts of art, culture, and nature in the NuArt Sculpture Park art gallery attracts the attention of theauthor to dig deeper into sequential experiences and their formation. This study aims to discuss the spatialsequences present in architecture through elaboration regarding the architectural elements that also shape andinfluence the spatial sequences in NuArt Sculpture Park.The type of approach used is descriptive qualitative research, where researchers will conduct aliterature study related to spatial sequences in architecture and its constituent elements in the form of bothphysical and non-physical elements which are then used as a basis for analyzing data. Then the data resultingfrom the qualitative analysis will be compiled and described narratively. The analysis process on the object ofstudy is then focused on elaborating existing paths and sketching at certain points to analyze the elements andtypes of spatial sequences that exist in NuArt Sculpture Park.From the research that has been done, it is concluded that this art gallery has spatial sequence formingelements as an ef ort to realize the main goals and concepts of NuArt Sculpture Park so that visitors get acomplete experience. Based on the relationship between music and architecture, the grooves in NuArt SculpturePark are bound by a unified sequence consisting of an intro, verse, chorus, bridge, and outro. Meanwhile, whenviewed from the spatial sequences in architecture, the types of sequences formed in NuArt Sculpture Park arelong sequences and short sequences.Key Words: spatial sequences, art gallery, NuArt Sculpture Park